Status of aquatic resources and their harvest from Someswari River in Northern Bangladesh - Chakraborty, Binay Kumar; Madhuri, Allu Venkata; Khatun, Arifa (Journal of the Inland Fisheries Society of India, 2021)
Bangladesh is very rich in aquatic biodiversity. The present study, conducted during 2015 to 2019, recorded a total of 139 species (109 fish, 09 prawn, 01 snail, 05 crabs, and 15 turtles) belonging to 22 families from the Someswari River of Bangladesh and its flood plain. Ten types of fishing gears, different crafts, hook and lines were found operative in the river. Increasing use of "current jal" (17.0-26.40%) and "Kapuri jal" (13.0-15.60%) were identified as detrimental gears destroying different species. The fish production has decreased drastically from 119.89Â±7.77 ton to 71.25Â±3.88 ton within four years. Four important aquatic species including major carp mahaseer (Tor tor) and reptiles (Cyclemys oldhami, Melanocheelys trjuuga and Morenia petersi) became rare and 17 commercially important species were at the edge of extinction (critically endangered, CR). From the study, 71 species were recorded in the endangered (EN) category, 21 species with vulnerable status (VU), 12 species with lower risk (LR), 08 species as least concern (LC) and 04 species as data deficient (DD). To save the existing aquatic species in the studied riverine ecosystem and ensure better livelihood of the fishers, a team of local management committee, similar to the hilsa fisheries management technology is needed. Key words Aquatic fauna, Biodiversity, Extinct, Endangered, Illegal fishing, Over exploitation.